METODE SPEOS (STIMULASI PIJAT ENDORPHIN, OKSITOSIN, DAN SUGESTIF) DALAM MENINGKATKAN PRODUKSI ASI IBU POST PARTUM - Ranida Arsi; Sri Rejeki; Achmad Zulfa (Indonesian National Nurses Association (INNA) of Central Java, 2021)
Background: Breast milk is the best food that babies need in the first 6 months of life. The success of exclusive breastfeeding is determined at the beginning of offering ASI on the first day of birth. Exclusive breastfeeding can be constrained by the limited production of breast milk. The SPEOS methods is an alternative to help increase breastfeeding. The SPEOS (Endorphin, Oxytocin, and Suggestive Massage Stimulation) methods is a combination of endorpine, oxytocin, and suggestive massage stimulation carried out sequentially which will feel relaxation that stimulates the brain to release endorphin, prolactin and oxytocin hormones, so that breast milk becomes smooth. In addition, it provides comfort to mothers, increases mother's confidence and removes blockages so that obstacles in breastfeeding can be resolved properly. Objective: To determine the effectiveness of the SPEOS methods in increasing breast milk production in post partum mothers. Method: A literature review through a review of nursing articles to identify SPEOS methods in increasing breast milk production. The databases used are Scopus, Medica Local Update, One Search and Google Schoolar. The journal source is obtained using a prism flow diagram as the database search flow. The article inclusion criteria used were articles related to the SPEOS methods and breast milk production in post partum mothers, articles in English and Indonesian, articles published in 2010 to 2020, and full text articles while the exclusion criteria were articles published over the past 10 years, the use of foreign languages other than English and Indonesian, not intervention studies and articles that are not full text. There were 7 articles that met the inclusion and exclusion criteria requirements. Results: This literature review shows that the SPEOS methods (Endorphin, Oxytocin, and Suggestive Massage Stimulation) effective in increasing breast milk production in post partum mothers. Conclusion: the SPEOS methods (Endorphin, Oxytocin, and Suggestive Massage Stimulation) effective in increasing breast milk production in post partum mothers.